Artistic Representations of Suffering: Rights, Resistance, and Remembrance. Mark Celinscak and Curtis Hutt - Alphen, Ernst van (Holocaust and genocide studies, 2024)
In this interdisciplinary book, historians, philosophers, religious studies specialists, literary critics, jurists, and cultural theorists discuss visual a